The protective effect of Capparis spinosa fruit on triptolide-induced acute liver injury: A metabolomics-based systematic study. (March 2022) - Yang, Tao; Wang, Yu-Lin; Zhang, Ya-Lei; Liu, Yu-Ting; Tao, Yan-Yan; Zhou, Hua; Liu, Cheng-Hai
Graphical abstract: Highlights: The hepatoprotective effects of C. spinosa fruit extract (CSE) on triptolide (TP)-induced hepatotoxicity was found. 19 metabolites identified were associated with TP treatment and 13 metabolites were altered relative to CSE intervention. CSE-H inhibited the activities of arachidonate 5-lipoxygenase-activating protein and choline kinase alpha in the liver. Abstract: The study aimed to investigate the hepatoprotective effects of Capparis spinosa fruit extract (CSE) on triptolide (TP)-induced hepatotoxicity in vitro and in vivo. In vitro, we used a TP-induced AML-12 cell injury model and flow cytometry to determine the cell survival rate after intervention with CSE. In vivo, acute liver injury was induced by intragastric administration of TP (1000 μg/kg) to C57BL/6 mice. Two experimental groups received CSE treatment at 0.9 g/kg (CSE-Low (L)) or 2.8 g/kg (CSE-high (H)). CSE-H can significantly decrease liver cell apoptosis and ameliorated TP-induced liver injury. Furthermore, 19 metabolites identified in serum were associated with TP treatment and the levels of 13 metabolites were altered relative to TP treatment after CSE-H intervention. TP increased the activities of arachidonate 5-lipoxygenase-activating protein and choline kinase alpha in the liver, while CSE-H inhibited their activity. In conclusion, the CSE has good hepatoprotective effects on TP-induced hepatotoxicity.